Histone demethylases in neuronal differentiation, plasticity, and disease. (December 2019) - Swahari, Vijay; West, Anne E
Highlights: Neuronal functions of the histone demethylases LSD1, Kdm6b, and Kdm5c. Evidence for potential non-enzymatic functions of the histone demethylases. Summarize neurological disease-associated mutations in HDMs. Abstract : For more than 40 years after its discovery, histone methylation was thought to be largely irreversible. However, the first histone demethylase (HDM) was identified in 2004, challenging this notion. Since that time, more than 20 HDMs have been identified and characterized, and many have been shown to have critical roles in organismal development, cell fate, and disease. Here, we highlight some of the recent advances in our understanding of the function of HDMs in the context of neuronal development, plasticity, and disease. We focus, in particular, on molecular genetic studies of LSD1, Kdm6b, and Kdm5c that have elucidated both enzymatic and non-enzymatic gene regulatory functions of these HDMs in neurons.